Physiotherapy of patients with atherosclerotic ischemia of the lower limbs undergoing aortobifemoral bypass implantation - Spannbauer, Anna; Berwecki, Arkadiusz; Chwała, Maciej; Mika, Piotr; Ridan, Tomasz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2014)
Aortobifemoral by-pass implantation (implantatio vasis artificialis aorto-bifemoralis) is one of the most commonly performed procedures in the treatment of chronic lower limb ischemia. Aortobifemoral grafting is recommended in the case of extensive atherosclerotic lesions involving the peripheral section of the abdominal aorta and/or external as well as common iliac arteries. Professional physiotherapy reduces the risk of thrombotic and pulmonary complications and promotes optimal recovery after an extensive surgical intervention. Physiotherapy of patients with lower limbs atherosclerotic ischemia undergoing aortobifemoral by-pass surgery is closely related with nursing and medical care.